Clinical features of affected males with X linked ocular albinism. - Charles, S J (1993)
Seventy four males affected by X linked ocular albinism (XLOA) from 19 pedigrees were examined to assess phenotypic variation and visual prognosis. Nystagmus was present in all cases except one. Best visual acuity ranged from 6/9 to 6/60; 79.7% could see 6/36 or better; most could read N5. Marked iris translucency and foveal hypoplasia were present in all cases. Posterior embryotoxon was present in 30% and dysplastic optic discs were often seen. Pigmentation of the posterior pole was associated with better visual acuity. XLOA is under-diagnosed: almost 20% of cases had been previously diagnosed as having congenital nystagmus until reviewed in this study.